2018
DOI: 10.1021/acs.inorgchem.7b02880
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Functionalized Al-MOF#@yxSm2O3–ZnO: A Visible Light-Driven Nanocomposite with Excellent Photocatalytic Activity for the Photo-Degradation of Amoxicillin

Abstract: A visible light-driven amine-functionalized Al-based MOF@ SmO-ZnO nanocomposite (NH-MOF@ SmO-ZnO NCP) was synthesized as an effective photocatalyst for AMX degradation in the presence of ultrasound, in which # is MOF synthesis conditions from MOF to MOF and x and y stand for the weight percentages of SmO-to-ZnO and SmO-ZnO-to-MOF, respectively. The β-lactam antibiotic AMX, which is widely used for treating Gram-positive and Gram-negative bacterial infections in both animals and humans, was employed as a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 94 publications
0
30
0
Order By: Relevance
“…Compared with PCN-700, the FT-IR spectra of PCN-700-B and PCN-700-MB displayed two apparent peaks at 3503 cm −1 and 3389 cm −1 in the high wavenumber area, resembling the bands of H 2 BDC-NH 2 at 3509 cm −1 and 3395 cm −1 , which could be ascribed to the asymmetric and symmetric stretching of the amine moieties in the complexes. 24,42,43 In contrast, for PCN-700-AB, the υ(N-H) characteristic peaks appeared at 3499 cm −1 , 3385 cm −1 , which was a slight shift, compared with H 2 BDC-NH 2 , and it was due to the additional electron-withdrawing groups, -COOH, of H 2 TPDC-(COOH) 2 , which occurred after the second step of the installation. In addition, the free carboxylic acid, -COOH, in PCN-700-AB has also been observed at ∼1703 cm −1 in the FT-IR spectra (see Supporting Information Figure S11).…”
Section: Resultsmentioning
confidence: 91%
“…Compared with PCN-700, the FT-IR spectra of PCN-700-B and PCN-700-MB displayed two apparent peaks at 3503 cm −1 and 3389 cm −1 in the high wavenumber area, resembling the bands of H 2 BDC-NH 2 at 3509 cm −1 and 3395 cm −1 , which could be ascribed to the asymmetric and symmetric stretching of the amine moieties in the complexes. 24,42,43 In contrast, for PCN-700-AB, the υ(N-H) characteristic peaks appeared at 3499 cm −1 , 3385 cm −1 , which was a slight shift, compared with H 2 BDC-NH 2 , and it was due to the additional electron-withdrawing groups, -COOH, of H 2 TPDC-(COOH) 2 , which occurred after the second step of the installation. In addition, the free carboxylic acid, -COOH, in PCN-700-AB has also been observed at ∼1703 cm −1 in the FT-IR spectra (see Supporting Information Figure S11).…”
Section: Resultsmentioning
confidence: 91%
“…From Fig. (a) it can be found that CuS/TiO 2 NBs and TiO 2 NBs exhibit the equivalent strong absorption in the UV region (below 400 nm), which might be attributed to the intrinsic band–band transition from the valence band to the conduction band of TiO 2 . The absorption intensity of CuS/TiO 2 NBs is stronger than that of TiO 2 NBs in the range from 400 to 800 nm, which is because of the existence of CuS nano‐particles.…”
Section: Resultsmentioning
confidence: 95%
“…For example, Abzari et al reported a visible light-driven amine-functionalized Al-based MOF nanocomposite (MIL-53(Al)-NH 2 @Sm 2 O 3 -ZnO) as an effective photocatalyst for amoxicillin (AMX) degradation. [77] The material achieved 100% removal rate of AMX in 90 min under visible light irradiation with a reliable recyclability. Another 2D photocatalyst, Fe 3 O 4 @ZIF-67, was reported by Guan's team, which could remove all of congo red under visible light radiation in 30 min.…”
Section: Catalysismentioning
confidence: 89%